EXPLORING DIDACTICISM IN ANITA NAIR’S “LIVING NEXT DOOR TO ALISE” - Savithri, K. Satya; Benny, N. Solomon (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Children’s literature is a crucial tool for imparting values, ethics, and life lessons, providing young readers with both entertainment and instruction. In her work, Living Next Door to Alise, Anita Nair illustrates this paradox, intricately intertwining a captivating narrative with didactic elements. This study examines the complex interplay between narrative and moral education in the book, concentrating on Nair’s treatment of empathy, community, individuality, and acceptance. From a didactic perspective, the paper analyses how the author constructs realistic events and complex characters to impart ethical teachings to her young audience in a subtle manner. Nair’s work is distinguished by its capacity to convey intricate concepts in an approachable and captivating way, steering clear of explicit moralization. Living Next Door to Alise showcases her ability to address universal issues, such as inclusion and appreciation of differences, while preserving regional nuances that resonate with Indian audiences. This research highlights the alignment of the narrative framework with children’s developmental needs and moral maturation, underscoring the importance of relatable circumstances in imparting values. This analysis, informed by theories of children’s literature and didacticism, demonstrates how Anita Nair establishes a dynamic interaction among plot, character, and moral instruction. It also examines how her work contributes to broader discourses about the purpose of children’s literature, especially within contemporary Indian contexts. This study underscores the importance of didacticism in fostering the emotional and ethical development of young readers, offering valuable insights into the evolving role of storytelling in children’s education.